Normative Defeaters and the Alleged Impossibility of Mere Animal Knowledge for Reflective Subjects. - Melis, Giacomo (Philosophia, 2023)
One emerging issue in contemporary epistemology concerns the relation between animal knowledge, which can be had by agents unable to take a view on the epistemic status of their attitudes, and reflective knowledge, which is only available to agents capable of taking such a view. Philosophers who are open to animal knowledge often presume that while many of the beliefs of human adults are formed unreflectively and thus constitute mere animal knowledge, some of them—those which become subject of explicit scrutiny or are the result of a deliberative effort—may attain the status of reflective knowledge. According to Sanford Goldberg and Jonathan Matheson (2020), however, it is impossible for reflective subjects to have mere animal knowledge. If correct, their view would have a number of repercussions, perhaps most notably the vindication of a dualism about knowledge, which would frustrate attempts to provide a unified account of knowledge-attributions to human adults, very young children, and non-human animals. I discuss Goldberg and Matheson's proposal, outline some of the ways in which it is insightful, and argue that it is ultimately unsuccessful because it neglects the inherent temporal dimension of knowledge acquisition. While the article is pitched as a reply to Goldberg and Matheson, its primary aim is to highlight significant connections between the debates on the relation between animal and reflective knowledge, propositional and doxastic justification, and the theory of epistemic defeat.